The Characteristics Of Proportionality Principle In Islamic Crowdfunding In Indonesia - Roro, Fiska Silvia Raden; Hernoko, Agus Yudha; Anand, Ghansham (Jurnal Hukum & Pembangunan, 2019)
Proportionality is a legal principle not only requires equility of the rights and obligations among parties based on competing values, but also has purpose to deliver justice among parties. This principle is in line with the Al Musawah principle in the Islamic contract or agreement which it also has the same goal: ad ‘adl wa tawazun. This principle is the implementation of the principle of good faith, the principle of transactions based on honesty including in terms of determining the profit margin. The research significance are to provide enhance knowledge about proportionality principle in Islamic crowdfunding in Indonesia, especially in financing contract in Islamic financial technology as a new business innovation scheme. This paper in order to promote the impartial perception and to harmonize the Islamic law and Indonesian laws. The type of the research is legal research. The research methods apply the conceptual approach to the the Islamic crowdfunding under proportionality principle in financing contract.